2007
DOI: 10.2109/jcersj.115.402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Analysis of the Strontium and Iron-doped Lanthanum Cobaltite Nano-powder Precursors

Abstract: Powders of perovskite-type oxides, with the general formula La 0.8 Sr 0.2 Co 1 x Fe x O 3 0.0 x 1.0 , were synthesized by the amorphous citrate method, and chemical reactions in such a synthesis process were systematically investigated via thermal analysis. A series of decompositions of citric acid derivatives occurred at 575-750 K, and the subsequent oxidation of metal-organic amorphous compounds to perovskite-type oxides occurred at 650-850 K. The apparent activation energies for those processes in La 0.8 Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The typical cation precursors for these perovskites are nitrates (Magnone et al 2007), occasionally prepared by dissolving the parent oxide in HNO3 (da Conceição et al 2009), although sometimes carbonates are used for the more basic cations (Fan and Liu 2009). Gupta and Whang also did a series of experiments where they changed between nitrates and acetates as precursors for the preparation of La0.9Sr0.1Cr0.85Fe0.05Co0.05Ni0.05O3−δ (Gupta and Whang 2007).…”
Section: Lanthanum Transition Metal Perovskite Oxides For Energy Techmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical cation precursors for these perovskites are nitrates (Magnone et al 2007), occasionally prepared by dissolving the parent oxide in HNO3 (da Conceição et al 2009), although sometimes carbonates are used for the more basic cations (Fan and Liu 2009). Gupta and Whang also did a series of experiments where they changed between nitrates and acetates as precursors for the preparation of La0.9Sr0.1Cr0.85Fe0.05Co0.05Ni0.05O3−δ (Gupta and Whang 2007).…”
Section: Lanthanum Transition Metal Perovskite Oxides For Energy Techmentioning
confidence: 99%
“…Phase-pure LSCF has been prepared by the amorphous citrate synthesis, without the use of EG (Magnone et al 2007;Fan and Liu 2009). On the other hand, Kakihana et al demonstrated that the polymerization was crucial in order to avoid secondary phases during the synthesis of lanthanum manganite ).…”
Section: Lanthanum Transition Metal Perovskite Oxides For Energy Techmentioning
confidence: 99%
“…In both case these results suggest that both Sm-Sr (y) and Co-Fe substitutions (x) has a strongly effect on crystallographic parameters of Sm 1-y Sr y Co 1-x Fe x O 3-δ solid solution series. In addition, the normalized pseudo-cubic lattice parameter composition-dependence of A 0.8 Sr 0.2 Co 1-x Fe x O 3-δ (RE=La and Pr) and Ba 0.5 Sr 0.5 Co 1-x Fe x O 3-δ solid solution series obtained from our measurments [11][12][13] O 3+δ end-members, but has probably solubility limit between x=0.2 and 0.1 [16].…”
Section: Resultsmentioning
confidence: 71%
“…In analogy with our earlier studies, where we have investigated the crystalline structure of A 1-y Sr y Co 1-x Fe x O 3-δ solid solution series for A=La [11], Pr [12], and Ba [13] in an attempt to understand the correlations between structure and and electrochemical properties of the materials, here we report the chemical synthesis and structural characterization of the Sm 0.8 Sr 0.2 Co 1-x Fe x O 3-δ solid solution series.…”
Section: +mentioning
confidence: 87%
See 1 more Smart Citation